2017
DOI: 10.1007/s11910-017-0765-7
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts of Memory Disorder in Epilepsy: Edging Towards a Network Account

Abstract: Some implications of a network conceptualisation of epilepsy include a need for more widespread cognitive phenotyping in epilepsy; recognition that memory disorders in epilepsy can be multi-determined, including by non-structural factors; deeper consideration given to the neurodevelopmental context in which memory problems emerge; the utility of new methods to characterise memory impairments in epilepsy; and a call for greater recognition of the close interrelationships between memory comorbidities and psychia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 87 publications
1
14
0
Order By: Relevance
“…These empirical findings, summarized in narrative, systematic and meta-analytic reviews ( Fonseca Wald et al, 2019 , Loughman et al, 2014 , Nickels et al, 2016 , Smith, 2016 , Wickens et al, 2017 , Wilson and Baxendale, 2014 ), appear complementary to modern neuroimaging studies detecting more extended than anticipated abnormalities in brain structure and connectivity within several epilepsy syndromes ( Keller et al, 2015 , Lin et al, 2007 , McDonald et al, 2008 , Nuyts et al, 2017 , Otte et al, 2012 , Slinger et al, 2016 , van Diessen et al, 2014 , Whelan et al, 2018 ), contributing to the contemporary perspective that neuropsychological abnormalities result from disruption in widely distributed cognition-dependent neuronal circuitry ( Rayner and Tailby, 2017 , Rayner et al, 2019 , Wilson and Baxendale, 2014 ).…”
Section: Introductionmentioning
confidence: 86%
“…These empirical findings, summarized in narrative, systematic and meta-analytic reviews ( Fonseca Wald et al, 2019 , Loughman et al, 2014 , Nickels et al, 2016 , Smith, 2016 , Wickens et al, 2017 , Wilson and Baxendale, 2014 ), appear complementary to modern neuroimaging studies detecting more extended than anticipated abnormalities in brain structure and connectivity within several epilepsy syndromes ( Keller et al, 2015 , Lin et al, 2007 , McDonald et al, 2008 , Nuyts et al, 2017 , Otte et al, 2012 , Slinger et al, 2016 , van Diessen et al, 2014 , Whelan et al, 2018 ), contributing to the contemporary perspective that neuropsychological abnormalities result from disruption in widely distributed cognition-dependent neuronal circuitry ( Rayner and Tailby, 2017 , Rayner et al, 2019 , Wilson and Baxendale, 2014 ).…”
Section: Introductionmentioning
confidence: 86%
“…16 In a large community-based questionnaire survey among PWE in the United States (n = 1023), between 40% and 50% of respondents reported that epilepsy affected their ability to think clearly, to remember, to concentrate, and their mental and emotional well-being. They may be related to dysfunction in the networks required for storage and or retrieval of memory, 17 to cerebral morphological changes, to psychiatric comorbidity and/or to the use of AEDs. They may be related to dysfunction in the networks required for storage and or retrieval of memory, 17 to cerebral morphological changes, to psychiatric comorbidity and/or to the use of AEDs.…”
Section: Cognitive Problemsmentioning
confidence: 99%
“…6 The possible causes of memory problems in PWE are complex and potentially multi-factorial. They may be related to dysfunction in the networks required for storage and or retrieval of memory, 17 to cerebral morphological changes, to psychiatric comorbidity and/or to the use of AEDs. We found that female gender was a risk factor for cognitive problems, even after controlling for increased psychiatric comorbidity.…”
Section: Cognitive Problemsmentioning
confidence: 99%
“…46 Increased local network segregation in focal epilepsy has been observed in focal epilepsy and interpreted as an attempt to isolate the epileptic network from the rest of the brain. 46 While such re-organisation might be protective, in the sense of minimising the propagation of epileptic activity throughout the brain, it may come at an important cost: namely, reduced network flexibility, with attendant effects on cognitive, emotional and behavioural functioning 47 (Fig. 4).…”
Section: Causes Of Reduced Network Flexibility In Tlementioning
confidence: 99%
“…(C) epileptogensis within a region of tissue (nodes enclosed by yellow border) can lead to isolation of the epileptogenic region from the remainder of the network. 46,47 This is achieved by dampening of edges to/from the epileptogenic region. This "firewalling off" of the epileptogenic region could disrupt task-dependent changes in connection strength that normally support cognitive function (absence of thick lines in right panel of (C), giving rise to the reduced PPIs observed here (in addition to increases in path length).…”
Section: Moving Beyond Structure-function Relationships Of Cognition mentioning
confidence: 99%